2019
DOI: 10.1155/2019/6041816
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Free Culture System for Spontaneous Human Mesenchymal Stem Cell Spheroid Formation

Abstract: Human mesenchymal stem cells (hMSCs) are widely used in clinical research because of their multipotential, immunomodulatory, and reparative properties. Previous studies determined that hMSC spheroids from a three-dimensional (3D) culture possess higher therapeutic efficacy than conventional hMSCs from a monolayer (2D) culture. To date, various 3D culture methods have been developed to form hMSC spheroids but most of them used culture medium containing fetal bovine serum (FBS), which is not suitable for further… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Then, the mRNA level of p21 and GAPDH was quantified using SYBR Premix ExTaq (TaKaRa, Tokyo, Japan) with the 2 −ΔΔCt method according to the manufacturer's instructions. The primer sequences are shown in Table 33–35 …”
Section: Methodsmentioning
confidence: 99%
“…Then, the mRNA level of p21 and GAPDH was quantified using SYBR Premix ExTaq (TaKaRa, Tokyo, Japan) with the 2 −ΔΔCt method according to the manufacturer's instructions. The primer sequences are shown in Table 33–35 …”
Section: Methodsmentioning
confidence: 99%
“…C 60 and CNTs showed a combined impact on suppressing viral symptoms, lowering viral intensity in apical tissues, and improving photosynthetic apparatus function [ 181 ]. Hao et al [ 241 ] showed that foliar application of 200 mg/L MWCNTs and reduced GO nanoparticles inhibited the growth of the plant pathogen Podosphaera pannosa , which causes powdery mildew in roses ( Rosa rugosa Thunb.) (Fig.…”
Section: Cnt Uptake and Defense Mechanism Against Environmental Stressesmentioning
confidence: 99%
“…While a majority of the literature is focused on BMSCs, 3D cultures have also been reported to enhance the survival, stemness, paracrine/immunomodulatory activity, and multi-lineage differentiation of oral tissue-derived MSCs ( Zhang et al, 2012 ; Lee et al, 2017 ; Moritani et al, 2018 ; Subbarayan et al, 2018 ). However, few studies have characterized MSC spheroids in xeno-free cultures to facilitate clinical translation ( Ylostalo et al, 2017 ; Dong et al, 2019 ). Therefore, the objectives of the present study were to establish xeno-free monolayer (2D) cultures of human GPCs in HPL, and subsequently, to test their osteogenic potential in 3D spheroid cultures in comparison to BMSCs.…”
Section: Introductionmentioning
confidence: 99%